Activity of bats (Chiroptera) in extensive livestock systems in the Colombian Caribbean - Chacón Pacheco, Julio Javier (2024)
Introduction: Extensive cattle ranching in tropical dry forest areas (TDF) has caused the transformation of natural ecosystems and altered the behavior of associated organisms, generating variation in activity patterns. In bats, the activity pattern is affected by the composition and vegetation structure of the ecosystem, and by the climatic season (dry and rainy). Objetive: In this study, the effect of conventional management systems (CS) and silvopastoral (SPS) of extensive livestock management on the bat activity patterns in the Colombian Caribbean was determined. Methods: The activity pattern of bats in TDF fragments associated with CS and SPS was compared within an annual cycle. The daily activity patterns of 11 species with records of more than 10 days in within management systems were determined. Results: Greater bat activity was recorded during the rainy season. We found that although bats show behavioral adaptation to the different management systems, in TDF fragments associated with SPS there is greater bat activity throughout the year, compared to the activity recorded in CS. Species with higher energetic requirements and degree of specialization (Phyllostomus hastatus, P. discolor and Glossophaga soricina) modified their activity patterns between CS and SPS management types. Conclusion: The TDF fragments associated in SSP, due to the vegetation composition and structure, probably favor the constant supply of resources suitable for the bats assemblage stability.